THE ROLE OF MARKETING COMMUNICATION THROUGH SOCIAL MEDIA IN IMPROVING THE BRAND IMAGE OF THE ISLAMIC UNIVERSITY OF KALIMANTAN MUHAMMAD ARSYA AL BANJARI BANJARMASIN - Mohammad Zainul; Ridha Septina Arini (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research aims to analyze the role of marketing communication through Instagram in enhancing the brand image of Universitas Islam Kalimantan Muhammad Arsyad Al Banjari (UNISKA MAB). The study adopts a qualitative descriptive method, utilizing interviews with social media administrators and content analysis of selected Instagram posts from the official account @uniska_mab. The findings reveal that UNISKA MAB strategically uses Instagram to highlight achievements, academic credibility, and spiritual values, thereby reinforcing a positive and trustworthy institutional image. Posts related to accreditation success, national recognitions, and faculty accomplishments are crafted with culturally resonant and emotionally engaging language. The study concludes that Instagram serves not only as an information platform but also as a powerful branding tool in the digital age. Future developments should include more interactive and audience-driven content to maintain engagement and strengthen emotional ties with the university’s brand.